Honour is in Contentment : Life before oil in Ras Al Khaimah (UAE) and some neighbouring regions - Lancaster, William & Fidelity (Berlin/NY; Walter de Gruyter GmbH & co. KG, 2011)
Based on interviews and field research, the authors explore the sets of ideas Arab tribespeople from Ras Al-Khaimah had about tribe and community; social and economic networks, and jural contracts for livelihoods and profits; their uses of their environments; the moral relations of credit, debt and labour; ruling; economic and political transformations; and ideas of regional history where conflicts were regarded as disputes over sets of ideas, and informal accounts of tribal and local histories.Published sources give a wider context to these ideas and events which show the great complexity and differing perspectives of 'life before oil' in the Gulf
English
Keywords: HN50-995 Social history and conditions. Social problems. Social reform- By region or countryUAE- Ras Al Khaimah